Transitions to Inpatient Medicine Clerkship's SOAP: Notes and Presenting on Rounds - Teena Hadvani; Erica Hubenthal; Lindsay Chase (MedEdPORTAL, 2016)
Abstract Introduction Students often do not feel prepared or comfortable with oral presentations, and their perception of the purpose and goal of oral presentations differs from that of educators. This educational gap was reported by our students so we created this session as a part of a Transitions to Clerkship course, which prepares medical students for their clinical rotations. Methods The format and content of the session allow students to participate, engage in discussion, and receive real-time feedback from a faculty facilitator in order to learn about daily progress/subjective, objective, assessment, plan (SOAP) notes and presentations in a small-group setting. The materials include a detailed lesson plan and agenda for facilitators, a packet of materials for student use during the session, and an example history and physical with a videotaped patient encounter that serves as the foundation for discussion regarding SOAP notes and presentations. We recommend an orientation for facilitators prior to the session to highlight materials provided and suggest methods for teaching to help minimize variability across the small groups. Results Overall, this session has been well received by students for the last 2 years. Students report feeling more at ease and better prepared for clinical rotations as a result of this session. Session evaluations confirm that this session has been extremely helpful for students; all areas of evaluation have averaged a score above 4.6 (out of 5). Discussion While there are many resources available related to oral presentations and clinical documentation, our materials are unique in that the focus of this session is to provide a small-group, interactive overview of SOAP notes and oral presentations within a single teaching session from a focused clinical scenario.